Effect of nanofiber as nanopore maker agent on the performance of clinker bricks - Arslan, Çağrıalp; Borazan, Ismail; Gençel, Osman; Erdoğmuş, Ertuğrul; Sutcu, Mucahit; Gençel, Osman; Erdoğmuş, Ertuğrul; Arslan, Çağrıalp (Elsevier Sci Ltd, 2022)
Nanomaterials have distinctive characteristics that may significantly change the properties and performance of the matrix material into which they are incorporated, even if they are used at low rates. Considering beneficial sides, the nanomaterials also have the potential to be evaluated in building materials. The effect of nanofiber additive as a nanopore maker in clinker brick was investigated first time in the literature in this study. The nanofiber content was between 0.5 and 2.5 wt% of the clinker bricks. The studies were carried out by firing the pellets at 950 degrees C for 2 h, which were prepared in a cylindrical shape. Physicomechanical and thermal characteristics of specimens were tested. SEM, EDS and XRD characterizations were applied to the brick specimens. It was found that apparent porosity, water absorption and LOI of the brick show an increment with the content of nanofiber while its density, compressive strength, and thermal conductivity values decline. Highly competitive results within the literature were gathered. Bulk density was comparatively low as 1.28 g/cm(3), thermal conductivity was improved as 0.257 W/mK with almost three times lower than without nanofiber content. Apparent porosity increased up to 49.8% at 2.5 wt% nanofiber content. However, the addition of 2 wt% nanofiber presented optimum results when the improvements on the porosity (+58%) and thermal conductivity (-203%) are considered. The compressive strength (10.4 MPa) was higher than the required value (7 MPa) for semi-structural applications. In the light of these promising results achieved in this study, nanofibers may be used as pore makers in clinker bricks.
Keywords: Clinker Brick; Nanofiber; Pore Making Material; Nanoporous; Thermal Isolation